2010
DOI: 10.1016/j.ydbio.2009.12.045
|View full text |Cite
|
Sign up to set email alerts
|

A new Dictyostelium prestalk cell sub-type

Abstract: The mature fruiting body of Dictyostelium consists of stalk and spore cells but its construction, and the migration of the preceding slug stage, requires a number of specialized sub-types of prestalk cell whose nature and function are not well understood. The prototypic prestalk-specific gene, ecmA, is inducible by the polyketide DIF-1 in a monolayer assay and requires the DimB and MybE transcription factors for full inducibility. We perform genome-wide microarray analyses, on parental, mybE− and dimB− cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…However, rather than inducing expression, it appears to repress it (Zhukovskaya et al, 2006). In response to DIF-1 DimB appears to act as an inducer for some genes and as a repressor for other genes (Yamada et al, 2010). Two other DNA binding proteins, STATc and GataC, respond to addition of DIF-1 by rapid entry into the nucleus where they affect differentiation of PstO and PstB cells (Fukuzawa, Abe and Williams, 2003; Keller and Thompson, 2008; Fukuzawa, 2011).…”
Section: Prestalk Signalsmentioning
confidence: 99%
“…However, rather than inducing expression, it appears to repress it (Zhukovskaya et al, 2006). In response to DIF-1 DimB appears to act as an inducer for some genes and as a repressor for other genes (Yamada et al, 2010). Two other DNA binding proteins, STATc and GataC, respond to addition of DIF-1 by rapid entry into the nucleus where they affect differentiation of PstO and PstB cells (Fukuzawa, Abe and Williams, 2003; Keller and Thompson, 2008; Fukuzawa, 2011).…”
Section: Prestalk Signalsmentioning
confidence: 99%
“…Upper cup cells are derived from ALCs as are lower cup and basal disk cells [27], [28]. The lack of β-galactosidase in the latter two cell types suggest its production was confined to the recently identified PstU cells [29]. Normal production of BzpR in upper cup or PstU cells may explain the “droopy” sori phenotype of bzpR null cells, as upper cup cells have been shown to function in lifting the spore mass up the stalk [30].…”
Section: Discussionmentioning
confidence: 99%
“…These terminally differentiated cells derive from non-committed prespore and prestalk precursors. The pioneering work of Williams, Kay, Firtel and others have shown that progenitors to both prestalk and prespore populations are heterogeneous (Gaudet et al, 2008;Williams, 2006;Yamada et al, 2010). Spatially restricted expression of gene patterns has been used to define very specific classes of prestalk cells (e.g.…”
Section: Discussionmentioning
confidence: 99%